A Highly Efficient Monophosphine Ligand for Parts per Million Levels Pd‐Catalyzed Suzuki–Miyaura Coupling of (Hetero)Aryl Chlorides. Issue 19 (17th March 2020) - Choy, Pui Ying; Yuen, On Ying; Leung, Man Pan; Chow, Wing Kin; Kwong, Fuk Yee
Abstract : A new indolylphosphine WK‐phos has been synthesized for Pd‐catalyzed Suzuki–Miyaura coupling of (hetero)aryl chlorides with (alkyl)arylboronic acids. Comprising this newly developed ligand with palladium(II) acetate, the resulting catalyst system was found to be highly effective in facilitating the reaction even when the catalyst loading reaches parts per million levels (e.g. 10 ppm). These examples represent one of the lowest catalyst loadings reported to date of employing monophosphine (e.g. Ar‐PCy2 ) for Suzuki–Miyaura reactions. The ligand geometry has also been well‐characterized by single‐crystal X‐ray crystallography. Abstract : A new indolylphosphine WK‐phos has been synthesized for Pd‐catalyzed Suzuki–Miyaura coupling of (hetero)aryl chlorides with (alkyl)arylboronic acids. The catalyst system with this new ligand was found to be highly effective in facilitating the reaction even at catalyst loading levels in the parts per million range (e.g. 10 ppm).